Melatonin behavior in restoring chemical damaged C2C12 myoblasts. Issue 6 (5th April 2016) - Salucci, Sara; Baldassarri, Valentina; Canonico, Barbara; Burattini, Sabrina; Battistelli, Michela; Guescini, Michele; Papa, Stefano; Stocchi, Vilberto; Falcieri, Elisabetta
ABSTRACT: It is known that, besides a wide range of functions, melatonin provides protection against oxidative stress, thanks to its ability to act, directly, as a free radical scavenger and, indirectly, by stimulating antioxidant enzymes production and mitochondrial electron transport chain efficiency. Oxidative stress is one of the major players in initiating apoptotic cell death in skeletal muscle, as well as in other tissues. Apoptosis is essential for skeletal muscle development and homeostasis; nevertheless, its misregulation has been frequently observed in several myopathies, in sarcopenia, as well as in denervation and disuse. Melatonin activity was investigated in undifferentiated C2C12 skeletal muscle cells, after exposure to various apoptotic chemical triggers, chosen for their different mechanisms of action. Cells were pretreated with melatonin and then exposed to hydrogen peroxide, etoposide and staurosporine. Morphofunctional and molecular analyses show that in myoblasts melatonin prevents oxidative stress and apoptosis induced by chemicals following, at least in part, the mitochondria pathway. These results confirm melatonin ability to act as an antioxidant and antiapoptotic molecule in skeletal muscle cells, thus suggesting a possible therapeutic strategy for myopathies involving apoptosis misregulation. Microsc. Res. Tech. 79:532–540, 2016 . © 2016 Wiley Periodicals, Inc.